Quantifying external load and injury occurrence in women's collegiate volleyball players across a competitive season - Taylor, J. B.; Barnes, H. C.; Gombatto, S. P.; Greenwood, D.; Ford, K. R. (The Journal of Strength and Conditioning Research, 2022)
Volleyball demands repetitive jumping, with high loads linked to risk of injury. The purpose of this study was to examine jumping demands and injury patterns throughout a women's volleyball season. Sixteen Division-I female volleyball players wore an accelerometer to record jump count (JC) and jump height during every practice and match throughout the season. Physical health was documented using a weekly modified Oslo Sports Trauma Research Center Overuse Injury Questionnaire (OSLO) and time-loss injuries were recorded. Multivariate analyses of variance were used to compare measures across phases of the season, between types of session (practice vs. match), and between injured and noninjured players (a = 0.05). Results showed the greatest training demands in the preseason with larger jump counts than during the nonconference, conference schedule, and postseason schedules (p < 0.001). Performance increased throughout the season with greater jump heights in the nonconference and conference schedule than in the preseason (p = 0.01). There were no significant differences in JC between practices (65.5 ± 30.5) and matches (67.5 ± 46.4). An injury incidence of 5.49 injures per 1,000 athletic exposures was identified, with injuries accounting for 31 days lost, or 2.1% of total exposures. Injuries affected performance throughout the season, as noted by an average weekly OSLO score of 15.1 ± 13.9%. Injured players had significantly lower jump counts per exposure (p = 0.03) and a larger variation in training load than uninjured players (coefficient of variation: injured = 54%, uninjured = 41%; p = 0.006). These data help provide coaches and clinicians for training and rehabilitation program designs.